2020
DOI: 10.1088/1755-1315/423/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Indonesia’s climate change national determined contributions, a farfetch dream or possible reality?

Abstract: As one of the Parties of the Paris Agreement, Indonesia is required to prepare and communicate its own National Determined Contribution (NDC) and maintaining successive nationally NDC which it intends to achieve. Indonesia has set unconditional reduction target by 29% and the conditional target up to 41% of the business as usual scenario by 2030. By setting these goals, Indonesia envisions achieving archipelagic climate resilience through comprehensive adaptation and mitigation programs and disaster risk reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Based on this study, Sulistiawati [24] has not found any local regulations that support the national strategy in implementing NDCs. Responding to these problems in Indonesia, Sulistiawati [24] suggested that the Indonesian Ministry of Environment and Forestry needs to reintroduce and socialize Indonesia's NDCs to local levels, encourage ways to reduce GHG, and combat climate change together. Furthermore, to achieve the NDCs, Panggabean [25] states that educational efforts are needed, not only for millennials and communities around forests or peatlands and the private sector but also for children.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Based on this study, Sulistiawati [24] has not found any local regulations that support the national strategy in implementing NDCs. Responding to these problems in Indonesia, Sulistiawati [24] suggested that the Indonesian Ministry of Environment and Forestry needs to reintroduce and socialize Indonesia's NDCs to local levels, encourage ways to reduce GHG, and combat climate change together. Furthermore, to achieve the NDCs, Panggabean [25] states that educational efforts are needed, not only for millennials and communities around forests or peatlands and the private sector but also for children.…”
Section: Resultsmentioning
confidence: 73%
“…Research from Sulistiawati [24] tries to describe local regulatory efforts to achieve NDCs targets at the local level of the Indonesian government by examining local government efforts in addressing climate change issues and meeting Indonesia's NDCs targets. Based on this study, Sulistiawati [24] has not found any local regulations that support the national strategy in implementing NDCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the method used in searching the relevant papers to be analyzed, sixteen (16) articles addressing the reduction of carbon emissions from buildings were obtained. Table 2 shows the list of the reviewed articles (by author, year, journal tittle, and references), 37…”
Section: Overview Of the Reviewed Articlesmentioning
confidence: 99%
“…By passing Law No. 16 of 2016, Indonesia officially became a party to the Paris Agreement, which outlined its climate pledges in the NDC document [16], aiming to limit global temperature rise below 1.5ºC [3]. Indonesia's path to achieving net-zero emissions involves reducing fossil fuel usage, promoting ecofriendly technologies, and increasing the use of renewable energy sources [17].…”
Section: Introductionmentioning
confidence: 99%